Analysis of the Implementation of Village SDGs Policies in Accelerating Village Development: A Case Study of Rambipuji Village - Suwarno Suwarno; Bambang Giyanto; Mala Sondang Silitonga (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Implementation of Village SDGs in Indonesia faces structural challenges such as limited village human resource capacity, poor data synchronization, and suboptimal inter-stakeholder coordination, as reflected in social facts showing many villages struggle to achieve clean energy targets (SDG 7) and climate resilience (SDG 13) due to high GHG emissions from deforestation and fossil fuels. Amid these issues, Rambipuji Village in Rambipuji Subdistrict, Jember Regency, successfully achieved high IDM scores and became a pilot village, particularly in SDG 7 and 13, positioning it as a role model for sustainable development. This qualitative descriptive study analyzes the process using George C. Edwards III's framework. Key findings indicate that implementation proceeds in a structural-participative manner through synergy among village officials, communities, and institutions, supported by clear bureaucratic structures, effective communication, and directed resource management; however, only 7 of 18 priority targets were realized, such as climate-responsive villages and clean energy initiatives. Supporting factors include commitment from officials and village funds, while barriers include limited human resources and suboptimal communication. Strengthening Edwards III's dimensions is recommended for optimizing national Village SDGs.